Intellectual Property in the Global Trading System EU-China Perspective - Shi, Wei.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Having explored multifaceted issues of IPR enforcement, this book argues that IPR enforcement problem is not an actual outcome of Confucian philosophy and "to steal a book" is not an "elegant offence." This book demonstrates that counterfeiting and piracy are common inevitable consequences of inadequate economic development and a by-product of a unique set of socioeconomic crises deriving from the development of a dysfunctional institutional regime. By examining areas of compatibilities between European and Chinese cultures and analysing painful lessons from the US-China negotiations over IPR protection, this book uses the prism of EU-China trade relations to suggest ways to reconcile the minimum standards of TRIPs Agreement and the specific conditions of particular states, and provide insight into the unresolved issues as to how and when China$1 (Bs WTO commitments will be implemented.s
The Justification for IPR Protection -- China$1 (Bs Response to the Multilateral Context of TRIPs -- Cultural Perplexity in Intellectual Property: How to Undo the Gordian Knot -- EU-China Interaction in Normative Integration -- Harmony or Coercion? EU-China Trade Relations and IPR -- Conclusion.s
Keywords: Law; Commercial law; Private international law; Conflict of laws; International law; Comparative law; Trade; Intellectual property -- Law and legislation; International economics; Law and economics; Law; Commercial Law; International Economics; International IT and Media Law, Intellectual Property Law; International Economic Law, Trade Law; Private International Law, International & Foreign Law, Comparative Law; Law and Economics; Electronic books